Global Burden of Thrombosis: Epidemiologic Aspects. Issue 9 (29th April 2016) - Wendelboe, Aaron M.; Raskob, Gary E.
Abstract : Thromboembolic conditions were estimated to account for 1 in 4 deaths worldwide in 2010 and are the leading cause of mortality. Thromboembolic conditions are divided into arterial and venous thrombotic conditions. Ischemic heart disease and ischemic stroke comprise the major arterial thromboses and deep-vein thrombosis and pulmonary embolism comprise venous thromboembolism. Atrial fibrillation is a major risk factor for stroke and systemic arterial thromboembolism. Estimates of the global burden of disease were obtained from Global Burden of Disease Project reports, recent systematic reviews, and searching the published literature for recent studies reporting measures of incidence, burden, and disability-adjusted life-years. Estimates per 100 000 of the global incidence rate (IR) for each condition are ischemic heart disease, IR=1518.7; myocardial infarction, IR=139.3; ischemic stroke, IR=114.3; atrial fibrillation, IR=77.5 in males and 59.5 in females; and venous thromboembolism, IR=115 to 269. Mortality rates (MRs) for each condition are ischemic heart disease, MR=105.5; ischemic stroke, MR=42.3; atrial fibrillation, MR=1.7; and venous thromboembolism, MR=9.4 to 32.3. Global public awareness is substantially lower for pulmonary embolism (54%) and deep-vein thrombosis (44%) than heart attack (88%) and stroke (85%). Over time, the incidence and MRs of these conditions have improved in developed countries, but are increasing in developing countries. Public health efforts to measure disease burden and increase awareness of symptoms and risk factors need to improve, particularly in low- and middle-income regions to address this leading cause of morbidity and mortality.